Extramedullary Motorized Lengthening of the Femur in Young Children. Issue 10 (November 2020) - Dahl, Mark T.; Morrison, Stewart G.; Laine, Jennifer C.; Novotny, Susan A.; Georgiadis, Andrew G.
Abstract : Background: Limb lengthening by distraction osteogenesis is now achievable via motorized intramedullary devices, mitigating many complications of lengthening by external fixation. In young patients, antegrade intramedullary nailing of the femur risks avascular necrosis of the femoral head. A method of extramedullary placement of a motorized expandable intramedullary nail has been employed by the senior author to safely achieve femoral lengthening without the use of an external fixator in young patients. Methods: Eleven skeletally immature patients with lower limb length discrepancy were reviewed who underwent extramedullary placement of a magnetic, expandable intramedullary nail for lengthening of the femur. Surgical details, lengthening parameters, and complications were reviewed and classified according to the modified Clavien-Dindo Classification. Results: Average lengthening was 32.3 mm (range: 27 to 40 mm) comprising an average 14.8% of femoral segment length. The average lengthening duration was 6.3 weeks, and average full weight-bearing began at 12.6 weeks. All but 1 patient underwent early removal of the device at an average of 4.5 months, and 5 had immediate plating of the femur. Complications rates were comparable to other methods of femoral lengthening, including varus or procurvatum through the regenerate, and unplanned reoperation in 3 of 11 cases. Preoperative considerations included careful planning of implant length due to short femoral segments and protection of the knee joint from contracture or iatrogenic instability. Conclusions: Extramedullary placement of a magnetic expandable intramedullary lengthening nail can achieve lengthening of the femur without the use of external fixation. Considerations with this technique include careful planning of implant length relative to trochanteric-physeal distance, protection against knee subluxation during lengthening, and mitigating deformity of the regenerate. Off-label, extramedullary use of these devices can be considered to decrease the burdens of external fixation in young children. The technique begs the advent of future all-internal technology specifically designed for safe limb lengthening in this age group. Level of Evidence: Level IV—retrospective case series. Abstract : Supplemental Digital Content is available in the text.